Pepsinogens to Distinguish Patients With Gastric Intestinal Metaplasia andHelicobacter pyloriInfection Among Populations at Risk for Gastric Cancer. Issue 7 (July 2016) - De Re, Valli; Orzes, Enrico; Canzonieri, Vincenzo; Maiero, Stefania; Fornasarig, Mara; Alessandrini, Lara; Cervo, Silvia; Steffan, Agostino; Zanette, Giorgio; Mazzon, Cinzia; De Paoli, Paolo; Cannizzaro, Renato
Abstract : OBJECTIVES: : The objectives of this study were to investigate the serum pepsinogen test for the prediction of OLGIM (Operative Link on Gastric Intestinal Metaplasia Assessment) stages in first‐degree relatives (FDR‐GC) of patients with gastric cancer (GC) and autoimmune chronic atrophic gastritis (ACAG). METHODS: : In 67 consecutive patients with ACAG, 82 FDR‐GC, and 53 controls (CTRL) without gastric disease (confirmed by biopsy), serum levels of pepsinogen 1 (PG1), pepsinogen 2 (PG2), G17, and the PG1/2 ratio were assessed by enzyme‐linked immunosorbent assay kit. All ACAG patients had positive antiparietal cell antibody levels, estimated by indirect immunofluorescence. Biopsies taken in duplicate from the antrum, corpus, and fundus were stained with Giemsa for Helicobacter pylori detection. Endoscopic detection of metaplasia was confirmed by histological diagnosis. Histological classification of OLGIM stages was applied by using the criteria of severity and topography of intestinal metaplasia (IM). RESULTS: : The highest discrimination capacity for distinguishing ACAG from other groups of patients was the gastrin G17 test. The lowest mean for PG1 and PG2 serum levels was found in ACAG. In multivariate analysis by age, PG1 and PG1/PG2 were independent prognostic factors for metaplasia, and PG2 also for the presence of a histological H. pylori infection. The serum PG1 level was significantly lower in individuals with IM at OLGIM stage >2 than in those with IM at OLGIM stage <2, resulting in a useful method for the prediction of OLGIM stage. With the inclusion of patient age at diagnosis in the prediction of ≥2 vs. 0–1 OLGIM stages, the receiver operating characteristic (ROC) curve at 47.9 ng/ml PG1 level reached a significant area under the curve (AUC) value (0.978, P <0.001). We also observed a slight difference in PG2 serum levels between histological H. pylori ‐positive and H. pylori ‐negative subjects (ROC AUC: 0.599). CONCLUSIONS: : This study demonstrated an important increase in gastrin G17 serum level in autoimmune gastritis. PG1 serum level corrected by patient age can be used in the management of patients at risk for GC with a high predicted probability of having an OLGIM stage ≥2. Using a cutoff of 47.9 ng/ml, PG1 testing in FDR‐GC and ACAG patients had a sensitivity of 95.83% and a specificity of 93.37. Although these results could be validated in a prospective study, the known importance of higher OLGIM stages in increasing the risk of GC development supports the rationale of proposing PG1 algorithm as a diagnostic tool for the selection of high‐risk FDR‐GC and ACAG patients at high‐risk stages for subsequent detailed endoscopic examination to detect dysplasia and asymptomatic GC. In addition, serum PG1 and PG2 levels could stratify patients based on both H. pylori infection and OLGIM risk in consideration of the increased acknowledge regarding the role of H. pylori in the progression of gastritis to GC.